PATHOGENESIS AND TREATMENT SCHEME OF RENAL DYSFUNCTION IN SYSTEMIC SCLEROSIS AND SYSTEMIC LUPUS ERYTHEMATOSUS - Madaminov Khudayberdi Atabekovich (Scholar Express Journals, 2025)
Systemic connective tissue diseases such as systemic sclerosis and systemic lupus erythematosus often result in significant renal complications. These kidney pathologies, including scleroderma nephropathy and lupus nephritis, are associated with immune dysregulation, the presence of autoantibodies, and cytokine-induced fibrosis or immune complex deposition. Early detection of renal dysfunction in these conditions is crucial due to their contribution to increased morbidity and mortality. This article explores the pathogenesis and clinical features of kidney involvement in both diseases and outlines contemporary treatment strategies, including the use of corticosteroids, cytotoxic drugs, and antihypertensive agents. Timely diagnosis and personalized therapy can significantly improve patient outcomes and reduce long-term complications.
Keywords: Systemic sclerosis; systemic lupus erythematosus; renal dysfunction